Clinical evaluation of platelet rich fibrin as barrier membrane in treatment of grade II furcation defects - B. Harshavardhana; Nitin Gupta; Spandana Reddy Vantary; Ankit Krishna (Journal of Indian Society of Periodontology, 2024)
Background and Objectives: Various guided tissue regenerative procedures have been used in treatment of furcation defects. A combination of various graft materials and barrier membranes have been used over a period of time. The present study was designed to test whether autologous platelet-rich fibrin (PRF) can be effectively used as a barrier membrane along with porous hydroxyapatite (HA) bone graft in the treatment of Grade II furcation defects. Materials and Methods: The present study was a split-mouth design, in which a total of thirty patients with bilateral grade II furcation defects in the mandibular molars were selected. On the control side, the furcation defect was treated using only HA bone graft and in the test side, the furcation defect was treated using a combination of HA bone graft and PRF as barrier membrane. The clinical and radiological parameters were recorded presurgically, postsurgical at 3 and 6 months, respectively, and the results were statistically analyzed and compared. Results: The furcation defects treated in the test side showed better healing and bone fill when compared to control side. The clinical parameters of the test and control sides when compared were found to be statistically significant. Conclusion: PRF can be effectively used as barrier membrane along with a graft material thus enhancing the regenerative potential of the graft material while regenerating the lost periodontal tissue in Grade II furcation defects.